Efeito do knockout da Mitofusina 1 sobre a fertilidade de oócitos murinos - Carvalho, Karen Freire (2018)
Fertility is directly related to oocyte developmental competence. In this context, oocyte mitochondria play a crucial role and have become an important target in assisted reproduction therapies. However, the molecular mechanisms underlying these mitochondrial effects are unknown. Therefore, the implications of the deletion of Mitofusin 1 (Mfn1 cKO) in murine oocytes was investigated in this project. Infertility of Mfn1 cKO females was characterized by interruption in oocyte growth and total failure in ovulation. Compared with wild type oocytes (WT), Mfn1 cKO oocytes showed mitochondria with abnormal ultrastructure, fewer cristae and a vesicular internal structure. Assays with BrdU incorporation by the granulosa cells reinforced the phenotype of blocked folliculogenesis, since the Mfn1 cKO group presented a decrease in the number of cells in replication. In addition, it was verified that this group shows a decrease, both in the oocyte and in the ovary, in the amount of transcripts of most genes analyzed, involved with oocyte-granulosa communication and folliculogenesis control. Important factors for the progression of folliculogenesis had their mRNA levels restored when Mfn1 cKO granulosa-oocyte complexes (GOCs) were co-cultured with denuded WT oocytes. To test whether were due to an imbalance in the expression of Mitofusin 2 (MFN2) relative to MFN1, MFN2 or MFN1 and MFN2 were overexpressed during GOC culture. It was observed that MFN2 overexpression inhibited oocyte growth, which was rescued by overexpression of both Mitofusins. Therefore, the infertility of females Mfn1 cKO seems to be related to an imbalance in the expression of MFN1 and MFN2. Consequently, Mfn1 deletion led to the inhibition of PI3K/AKT signaling pathways in the oocyte as well as the expression of GDF9, Bmp15 and Fgf8b, resulting in folliculogenesis blockage, as it affected oocyte-granulosa communication.